Происхождение удмуртского народа: [монография] / М. Г. Атаманов-Эграпи - Атаманов-Эграпи Михаил Гаврилович (Удмуртия, 2017)
Экземпляры: (20201014) / Инвентарный номер: 41573 / Цена: 3500.00 / Сис.шифр: 63.5(2=664.1) / Авт.знак: А 92 / ГРНТИ: 03.61.91 / ББК: 63.5(2=664.1)